Islamku, Islam anda, Islam kita : agama masyarakat negara demokrasi - Wahid, Abdurrahman; Anwar, M. Syafi'i (Jakarta : The Wahid Institute, 2006)
Thoughts of Abdurrahman Wahid, former Indonesian President, on Islamic religious practice in Indonesia
Includes bibliographical references
Keywords: Islam -- Indonesia; Muslims -- Indonesia